The impact of macrophage and microglia secreted TNFα on oncolytic HSV-1 therapy in the glioblastoma tumor microenvironment - Meisen, W Hans (Clin Cancer Res, 2015)
PURPOSE: Oncolytic herpes simplex viruses [oHSV] represent a promising therapy for glioblastoma [GB], but their clinical success has been limited. Early innate immune responses to viral infection reduce oHSV replication, tumor destruction, and efficacy. Here, we characterized the antiviral effects of macrophages and microglia on viral therapy for GB. EXPERIMENTAL DESIGN: Quantitative flow cytometry of mice with intracranial gliomas [± oHSV] was utilized to examine macrophage/microglia infiltration and activation. In vitro co-culture assays of infected glioma cells with microglia/macrophages were utilized to test their impact on oHSV replication. Macrophages from TNFα knockout mice and blocking antibodies were used to evaluate the biological effects of TNFα on virus replication. TNFα blocking antibodies were utilized to evaluate the impact of TNFα on oHSV therapy in vivo. RESULTS: Flow cytometry analysis revealed a 7.9 fold increase in macrophage infiltration after virus treatment. Tumor infiltrating macrophages/microglia were polarized towards a M1, pro-inflammatory phenotype and they expressed high levels of CD86, MHCII, and Ly6C. Macrophages/microglia produced significant amounts of TNFα in response to infected glioma cells in vitro and in vivo. Utilizing TNFα blocking antibodies and macrophages derived from TNFα knockout mice we discovered TNFα induced apoptosis in infected tumor cells and inhibited virus replication. Finally, we demonstrated the transient blockade of TNFα from the tumor microenvironment with TNFα blocking antibodies significantly enhanced virus replication and survival in GB intracranial tumors. CONCLUSIONS: The results of these studies suggest FDA approved TNFα inhibitors may significantly improve the efficacy of oncolytic virus therapy.